Application of matrix-assisted laser desorption/ionization time-of flight mass spectrometry in clinical testing and diagnosis - Xiong, Qiushuang; Guan, Haotong (Frontiers in Cellular and Infection Microbiology, 2025)
With the development of science and technology, new technologies are becoming more and more widely used in clinical testing. Matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) is a technology with fast detection speed, low cost and high throughput. Since 2009, it has gradually entered the global clinical laboratory, and has gradually become an indispensable tool in clinical testing work, especially in clinical microbiology laboratory. In today’s field of microbial identification, MALDI-TOF MS fingerprinting analysis has become a fast and efficient means to identify microorganisms by comparing and analyzing the fingerprint of characteristic and stably expressed proteins with the constructed common reference spectrum library at the genus and species level. In addition to bacterial species identification, proteomic-based mass spectrometry also plays an important role in bacterial resistance detection by detecting antibiotic modification and hydrolysis of antibiotics and detecting changes in fingerprint maps of drug-resistant strains and sensitive strains. In terms of gene analysis, the platform of combined with PCR and MALDI-TOF MS can be used to identify viral infections and mutations, as well as clinical diagnosis of genetic diseases, including quantitative analysis of gene expression, analysis of gene copy number variation (CNV), and single-nucleotide polymorphism genotyping. Isothermal amplification-based MALDI-TOF MS is also expected as a complement to large-scale viral outbreak screening modalities. MALDI-TOF MS has played an enormous role in the identification of pathogenic microorganisms, virulence analysis, detection of bacterial resistance, study of resistance mechanisms, and clinical diagnosis of genetic diseases since its application, and it has been widely used in the diagnosis of bacterial diseases, it has brought revolutionary changes to the clinical diagnosis field and the rational application of antibiotics. The application of MALDI-TOF MS in clinical laboratory has significant advantages compared with traditional methods, but it also faces some challenges. In the future, with the continuous expansion and optimization of fingerprint database and the development and improvement of industry standards, MALDI-TOF MS will play a more important role in the field of clinical microbial testing and even clinical diagnosis.